Adolescent aggressiveness of Korean pop fans viewed from celebrity worship tendencies - Panggabean, Tirza; Wulandari, Nawang Warsi; Taufiqurrahman, (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2024)
This study aims to determine whether celebrity worship influences the aggressiveness of young Korean pop fans. The research method used is quantitative. The sampling technique was accidental sampling with 100 respondents. The data collection method uses the aggressiveness scale and celebrity worship scale. Data analysis used simple linear regression analysis with the help of SPSS Ver.27. The results of hypothesis testing through simple linear regression with an F = 12.159 and a significant value of .001, with an r square of .110 it can be concluded that there is an influence between celebrity worship on aggressiveness of 11%.